2015
DOI: 10.5901/mjss.2015.v6n6p356
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of the Factors Affecting Pharmaceutical Consumption in Respect to Provinces in Turkey

Abstract: Pharmaceutical expense constitutes a great part of health service expenses. The increase in pharmaceutical consumption will also increase the health expenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This finding was consistent with the evidence from previous studies. 12,16,18 For instance, using Turkish data and quantile regressions, Alkan and Elmali 12 found that individuals aged ≥65 years spent more on pharmaceuticals than their younger peers. The explanation for these findings is straightforward.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding was consistent with the evidence from previous studies. 12,16,18 For instance, using Turkish data and quantile regressions, Alkan and Elmali 12 found that individuals aged ≥65 years spent more on pharmaceuticals than their younger peers. The explanation for these findings is straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…The independent variables were selected in light of the findings from previous studies related to consumption of pharmaceuticals, the theory of demand for health care, and the availability of data. [11][12][13][14][15][16][17][18][19] The independent variables consist of three main categories: (a) household heads' sociodemographic characteristics, (b) household profiles, and (c) the year of survey. A household head is a person in a household who makes important decisions on behalf of his/her household members.…”
Section: Independent Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…We attribute the above results to two factors. First, there is a signifcant diference in the share of drug expenditure in the total expenditure between outpatients and inpatients (Figure 3), so the increase in drug consumption increases health expenditure [22]. Figure 3 shows that prior to the ZMDP's implementation, outpatient and inpatient drug costs accounted for approximately 60% and 45%, respectively.…”
Section: Efect Of the Zmdp On Patient Expenditure Panel A Ofmentioning
confidence: 99%